2004
DOI: 10.1159/000081282
|View full text |Cite
|
Sign up to set email alerts
|

Poor Frequency Discrimination Probes Dyslexics with Particularly Impaired Working Memory

Abstract: Substantial difficulties in performing simple auditory discriminations were previously found in some individuals with a specific reading disability but not in others. This high variability in psychoacoustic performance raises the question of whether this difficulty is related to the reading deficit. Addressing this question, we compared adult dyslexics with and without difficulty in simple auditory discriminations, using 2-tone frequency discrimination as our probe. The distribution of their frequency discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
64
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 51 publications
10
64
0
1
Order By: Relevance
“…Consequently, the findings of the current study confirm our second hypothesis that dyslexic readers will perform poorly on tasks that require auditory temporal processing, independently from any deficit in working memory. Based on these findings, we conclude that the present study supports the hypothesis that dyslexic readers' deficit in auditory temporal processing is specific to temporal perception, and is not a product of a deficit in working memory, as it had been previously suggested (Ahissar, 2007;Banai & Ahissar, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, the findings of the current study confirm our second hypothesis that dyslexic readers will perform poorly on tasks that require auditory temporal processing, independently from any deficit in working memory. Based on these findings, we conclude that the present study supports the hypothesis that dyslexic readers' deficit in auditory temporal processing is specific to temporal perception, and is not a product of a deficit in working memory, as it had been previously suggested (Ahissar, 2007;Banai & Ahissar, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…However, the authors also found that working memory and auditory temporal resolution were not only poorer among dyslexic readers, but also were independently associated with their reading ability. Thus, it appears that both working memory and auditory temporal resolution are basic abilities that are involved in reading among dyslexic readers (Banai & Ahissar, 2004;Ben-Artzi et al, 2005;Reed, 1989;Tallal, 1980;Wright, Bowen, & Zecker, 2000). The complementary finding, which among the normal readers' performances on a digit span task and on a dichotic TOJ task did not predict reading ability, leads to the suggestion that working memory and auditory temporal resolution are utilized by the dyslexic in the processing associated with reading in a manner that is not used by the normal readers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some researchers suggested that working memory underlies the difficulties that dyslexic readers exhibit in auditory temporal resolution tasks, since it reduces the access to stored information (Banai & Ahissar, 2004). Several questions remain to be addressed regarding the reported deficits of dyslexic readers in working memory and auditory temporal resolution.…”
mentioning
confidence: 99%
“…However, in a series of subsequent studies (Ben-Yehudah et al, 2001;Amitay et al, 2002a;Amitay et al, 2002b;Banai and Ahissar, 2004;Ahissar et al, 2006;Banai and Ahissar, 2006) we found that their difficulties depend on task protocol more than on the complexity of stimulus or the perceptual resolution required. Specifically, while the general population performs substantially better when a limited set of stimuli is used repeatedly, individuals with D-LD display impaired 'anchoring' ability, and their thresholds remain high even with stimulus specific repetitions .…”
Section: Introductionmentioning
confidence: 86%